Attitude and Electricity-Saving Behaviors among Household Users of Electricity in Nsukka, Nigeria - Chinyere Theresa Ogbuanya (International Journal of Home Economics, Hospitality and Allied Research, 2023)
Household electricity consumption rates are increasing globally. However, saving electricity can decrease energy use, avoid wastage, and save financial resources for households. Therefore, this study was conducted to determine how attitude influences electricity-saving behaviors among household users in Nsukka District, Enugu State, Nigeria. The study adopted a descriptive survey design. A research question with corresponding null hypotheses was formulated and tested at a 0.05 level of significance. Stratified random sampling was used to select 400 household users, consisting of 206 females and 194 males. A structured questionnaire was used to collect information from the respondents. The questionnaire was validated by three experts and tested for reliability using the Cronbach alpha method. It contained respondents' personal data (biodata and demographics) and 28 items on attitudinal factors. The data obtained were analyzed to determine mean responses, and t-tests were used to test the null hypotheses at a 0.05 level of significance. The study found that gender does not influence the attitude of household users towards electricity-saving behaviors. It is recommended that government and non-government bodies organize training programs for household users of electricity to improve their attitude and promote more electricity-saving behaviors.